Seeing the unseen: discourse analysis of a Kristang ghost story in Singapore - Mok, Elaine Wai Man (Nanyang Technological University, 2023)
“Seeing the Unseen” is part of "Making Oral Languages Visible", a cross-disciplinary project that aims to preserve minority languages by adapting oral folktales into bilingual storybooks. The “unseen” in the title indexes (i) the Kristang language, a critically endangered Malay-Portuguese creole in Singapore and (ii) a ghost seen only by the story’s protagonist. Though ghost stories are perennially popular in Singapore, they comprise a nascent genre of study. While previous iterations of this project have focused on the artistic process, this paper offers a close textual analysis of the chosen Kristang folktale. In sum, the paper explores this question: what roles do ghost stories play in a storytelling medium?